2008
DOI: 10.1007/s00125-008-0955-6
|View full text |Cite
|
Sign up to set email alerts
|

The common SLC30A8 Arg325Trp variant is associated with reduced first-phase insulin release in 846 non-diabetic offspring of type 2 diabetes patients—the EUGENE2 study

Abstract: Of European non-diabetic offspring of type 2 diabetes patients, 46% are homozygous carriers of the Arg325Trp polymorphism in ZnT-8, which is known to associate with type 2 diabetes. These diabetes-prone offspring are characterised by a 19% decrease in first-phase insulin release following an intravenous glucose load, suggesting a role for this variant in the pathogenesis of pancreatic beta cell dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
89
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 25 publications
8
89
0
1
Order By: Relevance
“…Larger studies have also confirmed susceptibility loci within the SLC30A8, CDKN2A/B, IGF2BP2 and KCNJ11 genes as altering beta cell function, so larger studies may refine our initial estimates [7,11,12]. In conclusion, while individual susceptibility alleles only moderately alter pancreatic beta cell function, the risk is additively increased when risk alleles are combined.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Larger studies have also confirmed susceptibility loci within the SLC30A8, CDKN2A/B, IGF2BP2 and KCNJ11 genes as altering beta cell function, so larger studies may refine our initial estimates [7,11,12]. In conclusion, while individual susceptibility alleles only moderately alter pancreatic beta cell function, the risk is additively increased when risk alleles are combined.…”
Section: Resultsmentioning
confidence: 88%
“…The additive effects of the three risk variants were associated with a decrease in 30 min insulin response (p=4.17×10 −7 ). This was decreased by 43% in the 3.1% of the cohort with five or more risk alleles compared with the 3.2% that carried no risk alleles ( Although the other novel genes, CDKN2A/B, IGF2BP2, SLC30A8 and KCNJ11 have been shown to be associated with indices of pancreatic beta cell function in other studies [7,11,12], they did not reach statistical significance individually in our cohort [10]. However, when we included them in our additive model the relationships between increasing number of risk alleles and decreasing 30 min insulin response and decreasing beta cell glucose sensitivity still remained significant (p<0.001 and p=0.003, respectively).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…A polymorphism in SLC30A8 the gene encoding the ZnT8 transporter that mediates sequestration of zinc in secretory vesicles of pancreatic b-cells, is associated with both DM type 2 (DM2) (Boesgaard et al 2008;Jing et al 2011) and DM type 1 (DM1) (Gohlke et al 2008). It is unclear how the Znt8 polymorphism contributes to DM2 risk (Boesgaard et al 2008), but autoimmune dysfunction involving antibodies against Znt8 could contribute to DM1 (Wenzlau et al 2011).…”
Section: Zinc and Insulin Signaling In Diabetes Mellitus And Dementiamentioning
confidence: 99%
“…It is unclear how the Znt8 polymorphism contributes to DM2 risk (Boesgaard et al 2008), but autoimmune dysfunction involving antibodies against Znt8 could contribute to DM1 (Wenzlau et al 2011). Considering that zinc supplementation has clinical benefits in DM patients; research is needed to investigate if this polymorphism affects optimal zinc requirements.…”
Section: Zinc and Insulin Signaling In Diabetes Mellitus And Dementiamentioning
confidence: 99%